2010
DOI: 10.1021/ja105958p
|View full text |Cite
|
Sign up to set email alerts
|

Charge Localization in Isolated Mixed-Valence Complexes: An STM and Theoretical Study

Abstract: {Cp*(dppe)Fe(C≡C-)}(2)(1,3-C(6)H(4)) is studied both as a neutral molecule, Fe(II)-Fe(II), and as a mixed-valence complex, Fe(II)-Fe(III). Scanning tunneling microscopy (STM) is used to image these species at 77 K under ultrahigh-vacuum conditions. The neutral molecule Fe(II)-Fe(II) has a symmetric, "dumbbell" appearance in STM images, while the mixed-valence complex Fe(II)-Fe(III) demonstrates an asymmetric, bright-dim double-dot structure. This asymmetry results from localization of the electron to one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
89
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 48 publications
6
89
0
Order By: Relevance
“…[33][34][35] Among molecules with magnetic centres, ruthenium complexes may be of particular interest to study charge transfer or transport phenomena at the nanometer scale. [36][37][38][39][40][41][42] In a previous paper, we reported the investigation of a series of ruthenium tris( -diketonato)complexes by UHV-STM. 43 Here, the synthesis and characterization of a new ruthenium -diketonato complex with Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35] Among molecules with magnetic centres, ruthenium complexes may be of particular interest to study charge transfer or transport phenomena at the nanometer scale. [36][37][38][39][40][41][42] In a previous paper, we reported the investigation of a series of ruthenium tris( -diketonato)complexes by UHV-STM. 43 Here, the synthesis and characterization of a new ruthenium -diketonato complex with Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] A recent review also appeared on STM spectroscopy of magnetic molecules. [24] Several studies have been reported on ruthenium compounds measured by STM [25][26][27][28][29][30][31][32][33][34][35][36] and also on ruthenium and tris(diketonato) ligands, [37][38][39][40][41][42] but very few on adsorption of ruthenium or metal acetylacetonate (acac) complexes and their derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In particular, the wire-like performance of linear species has been investigated in detail by means of various physical methods 4 including scarce measurements at the molecular level. 3,5,6 Previous reports from our laboratory have described several series of this type of molecule containing the redox-active Cp*(dppe)Fe−CC− (dppe = 1,2-bis(diphenylphosphino)-ethane, Cp* = C 5 Me 5 ) termini linked to π-conjugated polyynediyl ligands ideally suited for studies of optical, electronic, and magnetic coupling between the redox centers. 7−11 It was also shown that introduction of aromatic rings such as benzene, naphthalene, anthracene, thiophene, or other bridges such as carboranes for instance in the polyynediyl spacer increases the chemical stability of the oxidized species and allows a fine-tuning of the coupling between the metal centers.…”
mentioning
confidence: 99%